The Process of Financial Development : A Statistical View From The FSAP Program - Ize, Alain, 1947- 1947- (The World Bank, 2008)
This paper uses a simple statistical approach to exploit some of the wealth of information contained in FSAP reports. The authors classify and count FSAP recommendations along a logical grid that reflects the fabric of financial activity and the ways in which states organize their policies in support of financial development. With some caveats reflecting the inherent limitations of the exercise, this analysis provides a simple monitoring tool to help understand the nature and evolution of the FSAP program. At the same time, it throws light on the nuts and bolts of the process of financial development and its inter-linkages with economic development. While many of the findings conform well to what one would expect, others are more surprising and also potentially more useful for understanding the inner workings of financial development